(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Hydrops fetalis is abnormal fluid accumulation within at least two fetal compartments, which may include pericardial effusion, pleural effusions, ascites, and skin edema. In the absence of red cell alloimmunization, hydrops fetalis is nonimmune (NHIF) and affects approximately 1 in 2000 pregnancies. Case presentation: A 33-year-old primigravida presented to the high-risk clinic for further management following an abnormal obstetric scan. Her antenatal follow-up was uneventful. She was blood group O, and rhesus positive. Physical examination was unremarkable. Abdominal examination revealed a fundal height of 32 weeks, which corresponded to her date. The first obstetric scan performed in the third trimester revealed a live baby with features of hydrops fetalis. Management included couple counseling, multidisciplinary discussion with a fetomaternal specialist, dexamethasone injection for fetal lung maturation, and expectant management. Discussion: The parents agreed to keep the pregnancy to term and plan for vaginal and cesarian deliveries reserved for obstetric indications. Nonimmune hydrops fetalis is associated with severe perinatal morbidity and significant maternal risk. The main causes of NIHF are chromosomal, fetal infection, and fetal cardiovascular problems. Conclusion: NIHF is rare, and a high index of suspicion is required for antenatal diagnosis. This affords parents tailored information and choices and supports multidisciplinary care with the additional aim of recognizing cases where fetal therapy may be appropriate, including timing for delivery.